The poor cannot participate in politics: the political-oligarchic pact and the criminalization of the poor in the Angolan socio-political landscape - EDUARDO SALA (RCMOS – Revista Científica Multidisciplinar O Saber, 2025)
Interdisciplinary in nature, this article uses qualitative research, specifically the critical document analysis method. It is a text that engages with different fields of knowledge, such as Sociology, Political Science, Legal Sciences, Geopolitics, and Education, from a dynamic of class relations under a popular and Afrocentric perspective. For documentary research, official documents from the Angolan state were used to gather socioeconomic data on the Angolan population, taking into account its variables. After a general discussion based on related literature, it was found that the political-oligarchic pact – the political criminalization of the poor – is a problem of conjunctural dimension in Angola. This means that, in addition to the members of the current regime (MPLA), under whom the greatest diagnosis of sadistic-social behavior syndrome falls, it also includes political figures and politically exposed persons affiliated with the main opposition party (UNITA), as well as political formations that present themselves as alternatives to traditional political parties.